PENERAPAN PENDIDIKAN AKHLAK MULIA DALAM MENGEMBANGKAN KARAKTER MELALUI METODE BERCERITA PADA ANAK USIA DINI (Studi Pada PAUD Non Formal An-Nuur) - Saepudin, Asep (PEDAGOGIA, 2014)
This study examines the application of noble character education in developing character through storytelling in early childhood in early childhood PAUD An-Nuur. The purpose of research is to obtain data on: 1) the implementation of the application of noble character education in developing character in early childhood in early childhood PAUD An-Nuur; 2) procedures for using storytelling in early childhood in the learning process in early childhood An-Nuur; 3) factors supporting and inhibiting the application of noble character education in developing character in early childhood in early childhood PAUD An Nuur. The results of the application of noble character education with the extent of the benefit of knowledge, attitudes, procedures use storytelling that students get as learners and their implementation in everyday life at school. To answer these problems the approach used in this study is a qualitative approach, the research procedure that produces descriptive data in the form of words written or spoken of people and observed behavior. Data collection techniques used were observation, interviews, documentation and study of literature. Research subjects in this study amounted to five informants, ie one person PAUD An Nuur, one early childhood tutor An Nuur, three students PAUD An Nuur. Based on data processing and discussion, the result of research on the application of noble character education in early childhood in early childhood PAUD An-Nuur, have the same goal, for the good of the child and make the child is given habituation noble with good morals. starts with giving good advice to exemplify good life so that children can imitate exemplary.Keywords: application of noble character education, character, storytelling